Populações tradicionais da Amazônia: um estudo de caso na vila do Aê, em São Caetano de Odivelas - Pará - LOBO, Quéren Hapuque Pantoja (2018)
This research describes the Aê village, in São Caetano de Odivelas city, located in the Northeast of Pará. The description is from the point of access and usage of natural resources. It highlights the richness of the environment and the fishing resources as important elements in the preservation of the people’s knowledge and lore. In this sense, it contributes to their definition and maintenance as a traditional people of the Amazon. The methodology used in this study consists in literature review, administration of a questionnaire with open and close ended questions, and direct observation of the object of study. It was noticed that there is an important correlation between the fishing practice and the extrativism with the local estuarine and mangroves ecosystem particularities. These practices are marked by a wealth production tied to the limits of nature logic, respecting its cycle and processes. However, the decrease of the fishing materials in the Amazon and the demographic profile of the village, which consists of only a few young people, compromise the conservation of this traditional people’s life style.